The Function of Child Protection Agencies in Upholding and Defending Children's Rights: The Function of Child Protection Agencies in Upholding and Defending Children's Rights - Ratnasari, Dewi (International Journal of Humanities, Law, and Politics, 2023)
The five pillars of parents, family, community, government, regional government, and the state are all strongly tied to child safety. The five of them are connected to one another as child protection organisers. All actions taken to ensure that children are treated fairly, have their rights upheld, are able to live, develop, and participate in society to the fullest extent possible, and are shielded from harm and discrimination, are collectively referred to as "child protection." The goal of child protection is to protect each child's rights. Child protection works in conjunction with other rights to ensure that kids have the things they need to live, grow, and thrive. However, in actuality, the situation of children in Indonesia is still quite worrying, particularly in regards to child labour, children living on the streets, and young people who have been sexually abused, exploited, or exploited for profit. In addition to being a violation of children's rights, the Child Protection Act also poses a significant threat to their survival and future development. However, the actual status of kids in Indonesia is still quite troubling, especially when it comes to child labour, kids living on the streets, kids who have been sexually abused, kids who have been sexually assaulted, and kids who have been the victims of commercial sexual exploitation. The Child Protection Act not only infringes on children's rights but also seriously jeopardises their survival and future growth.